MANAJEMEN KEPALA MADRASAH DALAM MENINGKATKAN LAYANAN BIMBINGAN KARIR SISWA - Mohammad Ja'far As-Shodiq (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2017)
The research is motivated by the experience through which students enteringand completing the achievement of objectives in accordance with the interest.Competence needs and aspirations. Thus career guidance is expected to havea sustainable management program development and in accordance with thedevelopmental characteristics of learners, ranging from kindergartens,primary schools, secondary schools, colleges, The focus of research in thisthesis are: 1) Head of planning madrassa in improving career guidanceservices, 2) the implementation of the Head madrassa in improvingstudents' career guidance services, 3) the evaluation of Head madrassa inimproving career guidance services. The research is a qualitative research,based on the discussion included descriptive study using a multi-site studydesign. Data collection techniques using participant observation, in-depthinterviews, and documentation. The analysis of data from data reduction,data presentation, and draw conclusions.Keywords: Management Principals, students Career Guidance Service.